The judge as political theorist : contemporary constitutional review - Robertson, David, 1946- (Princeton University Press, 2010)
The Judge as Political Theorist examines opinions by constitutional courts in liberal democracies to better understand the logic and nature of constitutional review. David Robertson argues that the constitutional judge's role is nothing like that of the legislator or chief executive, or even the ordinary judge. Rather, constitutional judges spell out to society the implications--on the ground--of the moral and practical commitments embodied in the nation's constitution. Constitutional review, in other words, is a form of applied political theory. Robertson takes an in-depth look at constitutio.